Simple green approach to reinforce natural rubber with bacterial cellulose nanofibers - Trovatti, Eliane; Carvalho, Antonio J. F.; Ribeiro, Sidney José Lima [UNESP]; Gandini, Alessandro (American Chemical Society (ACS), 2013)
Natural rubber (NR) is a renewable polymer with a wide range of applications, which is constantly tailored, further increasing its utilizations. The tensile strength is one of its most important properties susceptible of being enhanced by the simple incorporation of nanofibers. The preparation and characterization of natural-rubber based nanocomposites reinforced with bacterial cellulose (BC) and bacterial cellulose coated with polystyrene (BCPS), yielded high performance materials. The nanocomposites were prepared by a simple and green process, and characterized by tensile tests, dynamical mechanical analysis (DMA), scanning electron microscopy (SEM), and swelling experiments. The effect of the nanofiber content on morphology, static, and dynamic mechanical properties was also investigated. The results showed an increase in the mechanical properties, such as Young's modulus and tensile strength, even with modest nanofiber loadings. © 2013 American Chemical Society.
Keywords: Bacterial cellulose; Dynamic mechanical property; Dynamical mechanical analysis; Green process; High performance material; Young's Modulus; Cellulose; Coated materials; Elastic moduli; Nanocomposites; Rubber; Rubber applications; Scanning electron microscopy; Tensile strength; Tensile testing; Nanofibers; cellulose; nanocomposite; nanofiber; polymer; polystyrene; rubber; adsorption; bacterium; chemical modification; critical micelle concentration; Fourier transformation; green chemistry; infrared spectroscopy; loading test; material coating; materials; mechanical stress; morphology; nanotechnology; nonhuman; polymerization; priority journal; scanning electron microscopy; surface tension; tensile strength; thermogravimetry; Young modulus